2009
DOI: 10.1002/pen.21496
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior of polyamide 66‐based binary and ternary composites

Abstract: Friction and wear characteristics of polyamide 66 (PA66) and the composites of organoclay modified by styrene–ethylene/butylene–styrene triblock copolymer grafted with 1.84 wt% of maleic anhydride (SEBS‐g‐MA) were studied using an Universal Micro Tribometer reciprocating friction and wear tester. The morphologies of the wear tracks of PA66 and the composites were observed using a scanning electron microscope. The results showed that plastic deformation induced by the traction of the harder steel ball occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 13 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The wear behavior of a polymer in dry sliding condition is strongly influenced by its ability to form a transfer film on the counterface [30, 31]. The transfer films provide a shielding of the soft polymer surface from the hard metal asperities [15, 16, 32–35]. This study revealed that anti‐wear properties of PA 66/CB composites are improved markedly after incorporation of MoS 2 .…”
Section: Resultsmentioning
confidence: 92%
“…The wear behavior of a polymer in dry sliding condition is strongly influenced by its ability to form a transfer film on the counterface [30, 31]. The transfer films provide a shielding of the soft polymer surface from the hard metal asperities [15, 16, 32–35]. This study revealed that anti‐wear properties of PA 66/CB composites are improved markedly after incorporation of MoS 2 .…”
Section: Resultsmentioning
confidence: 92%